A peculiar type-I X-ray burst from GRS 1747-312 - in 't Zand, J.J.M.; Strohmayer, T.E.; Markwardt, C.B.; Swank, J. (EDP Sciences, 2003)
We report the serendipitous detection with the Rossi X-ray Timing Explorer of a long and peculiar X-ray burst whose position is consistent with one known X-ray burster (GRS 1747-312) and which occurred when that source was otherwise quiescent. The peculiar feature concerns a strong radius expansion of the neutron star photosphere, which occurred not within a few seconds from the start of the burst, as is standard in radius-expansion bursts, but 20 s later. This suggests that two different layers of the neutron star may have undergone thermonuclear runaways: a hydrogen-rich and a hydrogen-poor layer. The reason for the delay may be related to the source being otherwise quiescent.
Keywords: . accretion, accretion disks; globular clusters: individual: Terzan 6; – X-rays: binaries; X-rays: bursts; X-rays: individuals: GRS 1747-312